2022
DOI: 10.3390/ijerph192215351
|View full text |Cite
|
Sign up to set email alerts
|

Willingness of Tea Farmers to Adopt Ecological Agriculture Techniques Based on the UTAUT Extended Model

Abstract: Ecological agricultural technology is the key method for making the transition from traditional agriculture to ecological agriculture, and is also the basic measure for promoting the transformation and upgrading of the tea industry and sustainable development. This study explores the influencing factors and mechanisms of tea farmers’ adoption of ecological agricultural technology by using the extended model of the unified theory of technology adoption and use (UTAUT) based on perceived value. The analysis resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 46 publications
1
11
0
Order By: Relevance
“…The majority of Jiangxi Province's residents work in agriculture, and the province itself is mostly rural. It plays a significant role in the production of essential agricultural items such as grain, oilseeds, vegetables, and aquatic products [75], making it a prototypical agricultural province and one of China's 13 key grain-producing provinces. Jiangxi Province is a prime example of the classic Chinese agricultural style.…”
Section: Study Area and Sampling Methodsmentioning
confidence: 99%
“…The majority of Jiangxi Province's residents work in agriculture, and the province itself is mostly rural. It plays a significant role in the production of essential agricultural items such as grain, oilseeds, vegetables, and aquatic products [75], making it a prototypical agricultural province and one of China's 13 key grain-producing provinces. Jiangxi Province is a prime example of the classic Chinese agricultural style.…”
Section: Study Area and Sampling Methodsmentioning
confidence: 99%
“…In the context of the tea industry, Lou et al, through micro-level data analysis of tea farmers in the Dabie Mountain area, found that the adoption of green control technologies significantly increased agricultural income for farmers in mountainous areas [11]. Xie et al, based on survey data from tea growers in Fujian Province, revealed that the adoption of green production technologies increased the expected income of tea farmers [12]. Hu et al, in their study on the welfare level of tea farmers in the main tea-producing areas of Sichuan Province, found that the adoption of green control technologies significantly improved tea farmers' profits per mu of tea, disposable household income, and living consumption expenditure [13].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Tea growers often rely on chemical inputs to maintain high tea yields, but this practice poses significant risks to the environment, crops, and public safety. It can lead to issues such as soil erosion, soil acidification, pesticide residues, loss of soil organic carbon and in totality loss of biodiversity (Chen et al, 2022). To mitigate these risks, the application of modern agricultural practices, including conservation tillage, bio-char application, and soil and nutrient management, becomes crucial for sustaining a net-zero carbon sink and preserving soil biodiversity.…”
Section: Figurementioning
confidence: 99%